PSYCHOLOGICAL BASIS OF THE SPECIALISTS’ PROFESSIONAL TRAINING - Ivanova, N. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2019)
Retrospective aspects of the urgent issues of the psychological basis for the professional training of personality have been outlined. The basic stages of researches of this issue are listed, definition and contents of the psychological basis for the specialists’ training are determined.